ABC-TRIZ Introduction to Creative Design Thinking with Modern TRIZ Modeling - Orloff, Michael A.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This textbook arms the reader with powerful techniques of Modern TRIZ self-training and real problem solving. It is designed as a simple and efficient, step-by-step crash course in primary TRIZ models based on the author's methods of extraction and reinvention, or retrieval of invention models from any real-life objects. Special content addresses the psychological support of the person during problem solving and promotion of the new idea to realization. The book introduces the so-called Theory of Developing the Creative Personality (TDCP), initiated but not completed by Genrikh Altshuller, father of TRIZ and TDCP. The textbook continues to develop a simple standard model presentation of the problem solving process with a four-step Meta-Algorithm of Invention (MAI) T-R-I-Z. .
Miracle of Invention -- Towards the Modern TRIZ -- TRIZ Algorithms of Invention -- Modeling the Problem -- Extracting -- Inventing -- Reinventing -- Answers to Tests -- Operative Zone -- Directed Development of Systems -- The Origins of Creative Personality.
Keywords: Engineering design; Industrial engineering; Production engineering; Technological innovations; Engineering Design; Industrial and Production Engineering; Innovation and Technology Management